Bestimmung von individuellen Muskeleigenschaften durch mathematische Modelle und individuelle Simulation von einfachen sportlichen Bewegungen - Thaller, S.; Tilp, M. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft, 2003)
Mathematical models help to describe the connection between human intrinsic properties and simple sport movements. The stated model uses Hill`s force-velocity-relationship, an innervation function to describe neural activity and a geometric function to describe the anthropometrical conditions of the athlete. This allows to describe the individual movement of a leg extension. With the model it is on one hand possible to determine muscular properties of the leg extensors individually and on the other hand one can simulate extension movements. The method of muscle property determination is explained. Furthermore, examples are given to show that a mathematical model enables to confirm existing knowledge, to clarify controversies and to create new knowledge.